Subscribe to our Youtube Channel - https://www.youtube.com/channel/UCZBx269Tl5Os5NHlSbVX4Kg

Slide39.JPG

Slide40.JPG
Slide41.JPG Slide42.JPG Slide43.JPG Slide44.JPG Slide45.JPG

  1. Chapter 11 Class 11 Conic Sections
  2. Serial order wise

Transcript

Ex 11.1, 13 Find the equation of the circle passing through (0, 0) and making intercepts a and b on the coordinate axes. Let the equation of circle be (x – h)2 + (y – k)2 = r2 where (h, k) is the centre & r is the radius of a circle Also given that circle making intercepts a & b on the coordinate axes Let intercept on x-axis be a, So, coordinates of point A (a, 0) Let intercept on y-axis be b, So, coordinates of point B (0, b) Now, given that circle passes through (0, 0) So, Point (0, 0) will satisfy the equation of circle Putting x = 0 & y = 0 in (1) (0 − h)2 + (0 − k)2 = r2 h2 + k2 = r2 Also, point A (a, 0) lies on circle So, point A(a, 0) will satisfy the equation of circle Putting x = a & y = 0 in (1) (a − h)2 + (0 − k)2 = r2 (a − h)2 + k2 = r2 a2 + h2 − 2ah + k2 = r2 h2 + k2 + a2 − 2ah = r2 Putting h2 + k2 = r2 from (2) r2 + a2 − 2ah = r2 a2 − 2ah = r2 − r2 a(a − 2h) = 0 a − 2h = 0 h = (𝑎 )/2 Similarly, Point B(0, b) lie on the circle Point B(0, b) will satisfy the equation of circle Putting x = 0 & y = b in (1) (0 – h)2 + (b – k)2 = r2 h2 + (b – k)2 = r2 h2 + b2 + k2 − 2bk = r2 h2 + k2 + b2 − 2bk = r2 Putting h2 + k2 = r2 from (2) r2 + b2 − 2ah = r2 b2 − 2bk = r2 − r2 b(b − 2k) = 0 b − 2k = 0 b = 2k 2k = b k = (𝑏 )/2 Thus, h = (𝑎 )/2 & k = (𝑏 )/2 So, C(h, k) = (𝑎/2, 𝑏/2) Now we need to find radius of circle Putting h = 𝑎/2 & b = 𝑏/2 in (2) h2 + k2 = r2 (𝑎/2)^2 + (𝑏/2)^2 = r2 𝑎^2/4 + 𝑏^2/4 = r2 〖𝑎^2 + 𝑏〗^2/4 = r2 r2 = 〖𝑎^2 + 𝑏〗^2/4 Putting value of (h, k) & r2 in (1) (x – h)2 + (y – k)2 = r2 (𝑥− 𝑎/2)^2 + (𝑦−𝑏/2)^2 = 〖𝑎^2 + 𝑏〗^2/4 (x)2 + (𝑎/2)^2 − 2(x) (𝑎/2) + y2 +(𝑏/2)^2 − 2(y) (𝑏/2) = 〖𝑎^2 + 𝑏〗^2/4 x2 + 𝑎^2/4 − ax + y2 + 𝑏^2/4 − by = 〖𝑎^2 + 𝑏〗^2/4 x2 + y2 − ax − by + 𝑎^2/4 + 𝑏^2/4 = 〖𝑎^2 + 𝑏〗^2/4 x2 + y2 − ax − by + 〖𝑎^2 + 𝑏〗^2/4 = 〖𝑎^2 + 𝑏〗^2/4 x2 + y2 − ax − by = (𝑎2 + 𝑏2)/4 − 〖𝑎^2 + 𝑏〗^2/4 x2 + y2 − ax − by = 0 Which is required equation of circle

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.